2013
DOI: 10.1186/1752-4458-7-22
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to psychiatric care in urban north China: a general hospital based study

Abstract: BackgroundPathway studies highlight the help-seeking behaviors of patients with physical and mental illnesses. A number of studies in this field have been completed in various parts of the world. The purpose of this study is to explore the characteristics of the help-seeking pathways of patients with mental illness from urban north China at Mental Health Professional (MHP).MethodsThe pathway diagrams, which accounted for more than five percent of patients, were documented for 441 subjects using the translated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 33 publications
2
44
1
Order By: Relevance
“…Patients with higher levels of education may have better understanding of their own illness by participating in online support forums and reading articles about the traits of their illness, such as easy recurrence, the need for long-term medication, and prognosis, which may, however, also add to the perception of stigma, while patients with lower levels of education lack such knowledge. A recent hospital-based study of 441 patients with mental illness in the People’s Republic of China showed that stigma or lack of knowledge may hamper treatment of the mental illness 13. We hypothesized that the education level of schizophrenic patients may impact on the perception of internalized stigma.…”
Section: Introductionmentioning
confidence: 97%
“…Patients with higher levels of education may have better understanding of their own illness by participating in online support forums and reading articles about the traits of their illness, such as easy recurrence, the need for long-term medication, and prognosis, which may, however, also add to the perception of stigma, while patients with lower levels of education lack such knowledge. A recent hospital-based study of 441 patients with mental illness in the People’s Republic of China showed that stigma or lack of knowledge may hamper treatment of the mental illness 13. We hypothesized that the education level of schizophrenic patients may impact on the perception of internalized stigma.…”
Section: Introductionmentioning
confidence: 97%
“…In a study of 441 patients in urban northern China, the majority sought nonmental health pathways first rather than contacting mental HCPs directly. On average, each patient consulted 3.4 carers, and the vast majority first visited local tertiary general hospitals (56.4%) or local secondary general hospitals (24.8%) (Zhang et al ., ). Mental health stigmatizing attitudes in Japan are stronger than in countries such as Taiwan or Australia, possibly due to institutionalism, lack of national campaigns to tackle stigma, and/or society's valuing of conformity in Japan (Ando et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Many people regard mental illnesses to be caused by witchcraft and incurable to western medicines. This drives them away from seeking professional help [40, 41] and leads to poor adherence to prescribed medicines for those who attempt to go there [13, 42]. However, stronger discriminative intentions were reported not to necessarily prevent professional service use in Finland in case of a serious condition and having realistic views about medication [13, 43].…”
Section: Discussionmentioning
confidence: 99%